2022
DOI: 10.3390/lubricants10110311
|View full text |Cite
|
Sign up to set email alerts
|

Mixed EHL Problems: An Efficient Solution to the Fluid–Solid Coupling Problem with Consideration of Elastic Deformation and Cavitation

Abstract: For transient mixed Elastohydrodynamic lubrication (EHL) problems, a novel solution is required to predict friction loss and wear in sliding or rolling parts. However, existing solutions have numerous limitations. In general, the lower the oil film thickness is, the more serious the non-linear problem is. This paper presents an efficient solution to tackle the non-linearity of the mixed EHL problem. The elastic deformation in the fluid–solid iteration coupling problem is divided into two parts: One is induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Zhang et al [25] employed a PC average flow model for their mixed lubrication analysis and concluded that low roughness, larger asperity radius, and transverse roughness lay exhibit a lower coefficient of friction. Gu et al [18] employed a PC average flow model to study the transient mixed lubrication problem, and a good match was found with published experimental results (smooth surface with moving texture and rough surface with moving texture). Leighton et al [26] developed formulas for calculating flow factors (pressure, shear, and shear stress) for cross-hatched rough surfaces.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Zhang et al [25] employed a PC average flow model for their mixed lubrication analysis and concluded that low roughness, larger asperity radius, and transverse roughness lay exhibit a lower coefficient of friction. Gu et al [18] employed a PC average flow model to study the transient mixed lubrication problem, and a good match was found with published experimental results (smooth surface with moving texture and rough surface with moving texture). Leighton et al [26] developed formulas for calculating flow factors (pressure, shear, and shear stress) for cross-hatched rough surfaces.…”
Section: Introductionmentioning
confidence: 62%
“…To calculate the asperity contact pressure, various statistical and deterministic elastic and elastic-plastic contact models have been used [14][15][16][17]. Due to its easy implementation and fast computational ability, the average flow model based on PC (Patir and Cheng) flow factors has extensively been used for mixed lubrication analysis of conformal and counterformal contacts [18,19]. Despite having many advantages, average flow-based mixed lubrication models also have some limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the effect of the surface roughness on the lubrication performance can be realized by introducing the flow factor defined by Patir and Cheng [16] into the JFO model. The corresponding equation can be expressed as follows [17][18][19]:…”
Section: Lubrication Equationsmentioning
confidence: 99%
“…The detailed steps of the FBNS algorithm have been found in the work of Woloszynski et al 34 Interested readers can refer to these related works. 20,34,35 As shown in Figure 6, a GR (coarse to fine) strategy can be employed to obtain a further improvement in the convergence speed. In the GR strategy, the initial values in the high-layer grid are from the solutions of p and θ in the low-layer grid.…”
Section: Calculation Of Hydrodynamic Lubricationmentioning
confidence: 99%